Insurance vs takaful: A comparative analysis of fiqh opinion / Balqis Mohd Ramli … [et al.] - Mohd Ramli, Balqis; Mohd Nazri, Nur Ainaa Azmina; Yahaya, Nurul Aunni; Roslan, Nur Zulaikha; Wan Ramli, Wan Nurain Afiqah (2023)
This study discusses the differences between takaful products and conventional insurance products, especially general and insurance takaful, in terms of contract terms and conditions, market comparison, performance, market needs and distribution methods, major issues and challenges of each product in the selected country. Finally, find the article offers suggestions for amending takaful contracts that can increase the popularity of the target product in the market. To achieve this goal, the study examines the different legal documents of takaful insurance contracts and conventional insurance contracts.